Mate guarding in the spotless starling (Sturnus unicolor): Timing and duration pattern in intermediate breeding pairs (FOLIA ZOOLOGICA, 1997)
Mate guarding behaviour in the spotless starling Sturnus unicolor, a colonially breeding passerine was observed in five focal pairs of a nestbox colony in a Spanish `'dehesa'' (extensive pastured helm oak wood) in 1993. Daily observations were performed since the day of pair formation. Escorting behaviour began 4 days prior to laying and declined sharply between the 2 and 3 days of the laying period. Males followed their females more than the reverse, and spent more than 90% of time in the colony with the female during her fertile period. When escorting the females, males actively chased off other males to prevent them appproaching their mate. While males escorted females during fertile period up to 100% of times when they left colony, females came back to colony without their mate nearly 30% of times, showing that females succeeded in escaping their mate Vigilance when moving outside the colony. These results suggest that males guard in aim to keep other males away from their female, but also to keep females from approaching other males. Most of the observed copulations occurred during the guarding period. No extra-pair copulations (EPC) were witnessed between individuals of breeding pairs during the study time. One attempt of EPC occurred between a male of focal pair and a female of non-focal unstable pair. Nestbox occupation by unstable pairs and the shortness of time separating pair formation and laying in intermediate breeding pairs are discussed.